Implementasi Model Problem Based Learning Dalam Pembelajaran Di Sd - Sumilat, Juliana Margaretha; mokoagow, Vebrianty Yosua; mamonto, Gisca kurnia; harikedua, Deisye margarit; Lantu, Claudian. A,; pande, Frederik ajerhen (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research discusses the implementation of the Problem-Based Learning (PBL) model in the learning context in Elementary Schools (SD). The challenge faced in using the problem-based learning model is how teachers implement this problem-based learning model in high grades. PBL is integrated into the curriculum to increase student engagement and development of critical thinking skills in improving problem solving skills. The PBL method is implemented in various subjects with a focus on the use of mathematical case studies that are relevant to everyday life. Data was collected through classroom observations, interviews and documentation with students and teachers. Research shows that students are able to solve problems regarding understanding the material and increase student learning motivation. These results make a positive contribution to improving learning models in elementary schools (SD) and support the implementation of PBL as an effective learning approach in improving the quality of basic education.